Analisis Kesalahan Ejaan Dalam Karangan Teks Inspiratif Kelas IX SMP Negeri 7 Tasikmalaya - Dian Khoerani; Yasmin Tahani Inda Salam; Nurohmah Nurohmah; Ai Siti Nurjamilah (Pusat Riset dan Inovasi Nasional, 2024)
Mistakes in writing during learning have become common, especially for students who do not fully understand writing. Inspirational texts are texts that can inspire readers through the author's writing, whether through imagination or facts that occur in real life, containing inspiring content. The purpose of this analysis is to improve the writing structure of texts produced by ninth-grade students, who often write without paying attention to proper writing conventions. The research method used in this study is descriptive-analytical. The sampling method used is a single inspirational text created by a student as the research material. The results obtained from the research and analysis of these spelling errors include 12 categories, but there are still some identical words that were not included because they have already been categorized.